Analisis Kejahatan Pinjaman Online dalam Hukum Siber di Indonesia (Studi Kasus atas Putusan Nomor 2078/PID.SUS/2021/PN LBP) - Leo Yoga Wijaya; Nurmalia Ihsana; Punta Yoga (PT Elaborium Elevasi Indonesia, 2023)
Technological advances in the economic sector, one of which is the existence of financial technology in the form of digital peer to peer lending platforms or what is commonly referred to as online loans. The convenience offered by online loans is very tempting to the public so that many people use online loan services. These online loans are also regulated in an institution called the Financial Services Authority or OJK. Online loans that are registered or have operational permits from the OJK are Legal Online Loans, while Online Loans that are not registered or do not have an operational permit from the OJK are called Illegal Online Loans. In collecting debts, illegal online loans have committed crimes. The author focuses on illegal collection actions related to online loans from illegal financial technology as stated in Decree Number 2078/Pid.Sus/2021/PN Lbp. When collecting an online loan from the victim, the defendant sent electronic information containing threats of violence or intimidation addressed personally. Of course this action is very troubling society. The problem raised by the author in this paper is how the act of collection by Illegal Online Loans can be called a Cyber ​​Crime and how to handle and provide legal protection for victims of Cyber ​​Crime in the Study of Cyber ​​Law in Indonesia. The writing method used is normative research with a statutory approach.